Implementasi Sanksi Daftar Hitam Terhadap Penyedia Dalam Pengadaan Barang/Jasa Pemerintah - Mukti, Danu Tejo; Yasniwati, Yasniwati; Rosari, Anton (Faculty of Law, Andalas University, 2024)
This research aims to analyse the implementation of Blacklist Sanctions in Government Procurement, analyse the factors that can caused Providers who are subject to Blacklist Sanctions to sign contract with PPK, analyse sanctions for negligence of Procurement Actors from the Government and Legal Actions that can be taken by Service Providers subject to Blacklist Sanctions. This research adopts a normative-empiric and descriptive approach, utilizing a statute approach to legal provisions and equipped with empirical data. Research results: the implementation of Blacklist Sanctions is carried out by determining and displaying Blacklist Sanctions on the National Blacklist Portal, the sanctions are valid from the date of the Decree of Determining Blacklist Sanctions, Blacklist Sanctions do not apply retroactively (non-retroactive). The factors that can cause the Providers who are subject to Blacklist Sanctions to signed contract with PPK, among others any mistake is found in the evaluation process carried out by Selection Committee, PA/KPA being late in displaying Blacklist Sanctions on the National Blacklist Portal and the Blacklist Sanctions for Provider not appearing due to system errors. Government Procurement Actors may be subject to administrative sanctions for their negligence in contract with providers who are subject to Blacklist Sanctions. Providers can take legal action in the form of objections, postponements and cancellation of Blacklist Sanctions in accordance with applicable regulations.